Enhancing interest in science: exemplars as cues to communal affordances of science. Issue 11 (21st June 2016) - Clark, Emily K.; Fuesting, Melissa A.; Diekman, Amanda B.
Abstract: A deterrent to recruiting students into STEM pathways is the stereotype that STEM fields do not afford communal goals to work with or help others. We investigate the challenges to cueing communal opportunities in science via brief exposure to scientist exemplars. Both male and female scientists depicted as engaged in communal work increased beliefs that science afforded communal goals and positivity toward science careers (Study 1). Without the direct performance of communal activities, communal affordances were cued only when a female scientist was prototypic of her gender category and respondents were highly communally oriented (Study 2). To change stereotypes that science does not involve communal goals, both female and male scientists can highlight communal aspects of their work.